Changes in Volume and Density Parameters Measured on Computed Tomography Images Following Stereotactic Body Radiation Therapy of Nonspine Bone Metastases. (19th July 2019) - Finkelstein, Samuel; Raman, Srinivas; Van Der Velden, Joanne; Zhang, Liying; Tan, Carolyn; Dhillon, Amanpreet; Tonolete, Frances; Chiu, Nicholas; Probyn, Linda; McDonald, Rachel; Sahgal, Arjun; Chow, Edward; et al.
Introduction: Volumetric and density parameters measured from computed tomography scans were investigated for evaluating treatment response of nonspine bone lesions following stereotactic body radiation therapy. Methods: Twenty-three patients treated with stereotactic body radiation therapy to nonspine bone metastases with pre- and post-treatment radiological follow-up with computed tomography imaging were identified in a retrospective review. An expert radiologist classified 26 lesions by type (lytic, sclerotic) and by response. Two independent radiation oncologists created separate contours of the bone and soft tissue lesion volumes. Density and volume were assessed relative to baseline values. Results: For bone-only lesions, all lesions designated as local control decreased in volume or remained within 20% of baseline volumes. Lytic lesions classified as progressive disease exhibited much larger volume increases. Lytic bone lesions showed indications of remineralization with some exhibiting immediate increases in density (1-6 months) and others decreasing initially then increasing back toward baseline between 7 and 12 months. The majority of sclerotic lesions, all classified as local control, decreased slightly in both volume and density. Lesions with both soft tissue and boney involvement resulted in contradictory results when employing both radiological and size parameters for assessing treatment response. Classification was dominated by changes in soft tissue volume, despite associated volume or density changes in the corresponding boney lesion. In contrast, when soft tissue volume changes were minimal (<20% increase), classification appeared to be related primarily to density changes and not bone volume. Conclusions: Volume and density changes show promise as quantitative parameters for classifying treatment responses of nonspine osseous lesions. Further work is required for clarifying how these metrics can be applied to lesions with both boney and soft tissue components.